Acid-promoted synthesis of pyrazolo[4, 3-c]quinoline derivatives by employing pyrazole-arylamines and β-keto esters via cleavage of C–C bonds. Issue 18 (17th September 2022) - Jiang, Rui; Mu, Yangxiu; Zhang, Wei; Hong, Yu; Iqbal, Zafar; Hou, Jing; Yang, Zhixiang; Tang, Dong
Abstract: An approach for the synthesis of pyrazolo[4, 3-c]quinoline derivatives has been developed by the combination of pyrazole-arylamines and β-keto esters via cleavage of C–C bonds. The strategy shows good tolerance and compatibility with a wide range of functional groups. Moreover, this method features simple conditions, generates a series of alkyl substituted pyrazolo[4, 3-c]quinoline, and provides the desired products in moderate to good yields. Graphical Abstract: UF0001